PENGARUH ETIKA AUDITOR DAN FEE AUDIT TERHADAP KUALITAS AUDIT STUDI PADA KANTOR AKUNTAN PUBLIK DI KOTA MAKASSAR - Lusiana Kanji; Andi Kusumawati; Kartini Kartini (STIE AMKOP, 2019)
Lusiana Kanji (2019). Effect of Auditor Ethics and Audit Fee on Audit Quality Study at the Public Accountant Firm in Makassar City. The aim of this study to find out auditor ethics and audit fee on audit quality study at the public accountant firm in Makassar city. Data collection uses primary data obtained from questionnaires using saturated sample techniques. The population used in this study were all auditors who worked in the Public Accounting Firm in the city of Makassar, while the sample of this study amounted to 40 auditors. The results of the questionnaire have been tested for validity and reliability, also been tested classical assumption in the form of normality assumptions and assumptions of heterocedasticity. Data analysis method uses multiple linear regression techniques. The results of this study provide empirical evidence that the ethics of auditors and audit Fees positive effect and significant on audit quality at the Public Accountant Firm in Makassar City, ethiccs of auditor positive effect and significant on audit quality at the Public Accountant Firm in Makassar City, and audit Fee negative effect and not significant on audit quality at the Public Accountant Firm in Makassar City. Keywords : Auditor Ethics, Audit Fee, Audit Quality.